Cognitive Linguistics and its interpretation in grammar - Jumanazarov Samandar UrinovichJumanazarov Samandar Urinovich; Aliqulov Jahongir Jamol o’g’li; Sharopov Ulug’bek Sharipovich (Research Parks Publishing LLC, 2020)
The relationship between human events and events is closely linked to the practical application of the theory of cognitive theory. In fact, we can think of things that are happening in the real world - subjects, events, phenomena, based on our experience, knowledge and skills that have been generated over the years and, in this context, we will achieve a great deal of loyalty